Healing from Dry Bones: Creative Expression as a Way of Knowing in Diabetes Care - Heather L. Stuckey (Adult Education Research Conference, 2007)
A creative, action research process incorporated the use of metaphor and imagery in patient education to help illustrate the experience of living with diabetes through multiple ways of knowing. Findings and implications for practice in adult education and patient care are discussed.